2010
DOI: 10.1038/ejcn.2010.66
|View full text |Cite
|
Sign up to set email alerts
|

Specific adipocytokines profiles in patients with hyperactive and/or binge/purge form of anorexia nervosa

Abstract: Objective: The aim of our study was to determine whether eating behaviors and/or physical activity level may explain contradicting results in adipocytokines levels in anorexia nervosa (AN). Subjects/Methods: Fasting levels of circulating adipocytokines (adiponectin, resistin and leptin), insulin, glucose, C-reactive protein, cytokines (tumor necrosis factor-a and interleukin (IL)-1b), body composition and resting energy expenditure were measured in 24 women AN patients and 14 women controls. These parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
4
14
3
1
Order By: Relevance
“…However, there was a non-significant tendency towards higher values of adiponectin in AN women independently of the disease phase when compared to the healthy controls. These results are in agreement with those reported by Nogueira et al [26] and Amitani et al [27]. Moreover, in another study conducted by the group of Iwahashi, individuals diagnosed with AN showed a tendency towards higher adiponectin levels than in the control group.…”
Section: Prace Oryginalnesupporting
confidence: 83%
See 1 more Smart Citation
“…However, there was a non-significant tendency towards higher values of adiponectin in AN women independently of the disease phase when compared to the healthy controls. These results are in agreement with those reported by Nogueira et al [26] and Amitani et al [27]. Moreover, in another study conducted by the group of Iwahashi, individuals diagnosed with AN showed a tendency towards higher adiponectin levels than in the control group.…”
Section: Prace Oryginalnesupporting
confidence: 83%
“…The authors reported no correlations between concentration of resistin with disease duration and weight restoration [18]. In the study conducted by Nogueira et al no significant difference in serum resistin values was seen in the whole AN group when compared with healthy control women [26]. Housova et al did not reveal any differences in resistin concentration when comparing malnourished individuals with restrictive and the binge/purge subtype of AN with the controls [31].…”
Section: Prace Oryginalnementioning
confidence: 81%
“…Brain-derived neurotrophic factor The brain-derived neurotrophic factor (BDNF) was originally characterized as a member of the neurotrophin family implicated in the processes of neuronal outgrowth and differentiation, Iwahashi et al (2003), , Tagami et al (2004), Housova et al (2005), Dostálová et al (2007), Dolezalova et al (2007), Nogueira et al (2010) Plasma adiponectin →↓↑ → →↓↑ Cholecystokinin (CCK) Geracioti et al (1992), Tamai et al (1993), Lydiard et al (1993), , Brambilla, Brunetta, Draisci, et al (1995), Fujimoto et al (1997), Walsh (2002), Cuntz et al (2013) Nedvidkova et al (2003), Tanaka, Naruo, et al (2003), , Tanaka, Narau, et al (2003), Nakai et al (2003), Hotta et al (2004), Misra et al (2004), Troisi et al (2005), Otto et al (2005), Stock et al (2005), Kojima et al (2005), Harada et al (2008), Monteleone, Fabrazzo, Tortorella, et al (2005), , Monteleone, Castaldo, et al (2008), , Monteleone et al (2009), Sedlackova et al (2011 Total plasma ghrelin ↑ → ↑ → Total plasma ghrelin (response to test meal or OGT)…”
Section: →↓mentioning
confidence: 99%
“…Hipotalamusta leptin gibi vücut ağırlığını düzenlemede rol oynayan bir diğer molekül olan adiponektin düzeyleri anoreksiya nervoza tipine göre değişmektedir. [32,33] İlginç olarak, anoreksiya nervozalı hastalarda dolaşımdaki iştah açıcı bir nöropeptid olan AgRP düzeyi yüksek bulunmuş ve AgRP'nin kodlama bölgesindeki bir polimorfizmin anoreksiya nervoza ile ilişkili olduğu gösterilmiştir. [34] Çok yeni bir araştırma-nın sonuçlarına göre, her biri farklı dokuda salınan ve bir kısmının glukoz ve yağ asidi metabolizmasında ayrı ayrı önemli rolleri olan 15 üyeli bir hormon ailesi, C1q/TNFilişkili proteinler, (CTRP1-15) tanımlanmıştır.…”
Section: Merkezi Nöropeptid Sistemleriunclassified